Competing discourses as barriers to change in rehabilitation nursing: a discourse analysis - Angel, Sanne; Steensgaard, Randi; Kolbaek, Raymond; Frimann, Søren (Frontiers in Rehabilitation Sciences, 2023)
Introduction The power of action research to create change by anchoring research results in practice was challenged in an action research project at a specialized rehabilitation unit for persons with acquired spinal cord injury. Despite the co-researchers' new insights, approaches, and actions supporting patient participation, it was not possible to change the basic conditions for the practicing of nursing. We aimed to raise awareness of the mechanisms that govern barriers by exploring these barriers as experienced by nurses in their effort to change their practice to improve patient participation. Method We used Fairclough's critical discourse analysis drawing on Foucault's practical systems; ethics (identity, relation to oneself), power (action, relation to others), and knowledge (representation, aspects of the world), which he combines with discourse-analytical concepts. Results Our discourse analysis of the empirical data at micro-level uncovers the nature of barriers to change in practice. In addition, our analysis at macro-level unveils how these practices are embedded in larger historical, societal, and institutional discourses. This identified two current discourses: a biomedical discourse and a biopsychosocial discourse. In the light of these two discourses, the nurses at micro-level saw themselves as strong agents for the best rehabilitation by acting in accordance with the biopsychosocial discourse. But they were unable to find the time and space to do so due to tasks, structures, and practices specified by an organization dominated by the biomedical discourse.